Increased Incidence of Second Malignancies Associated with Small Bowel Adenocarcinoma - Dianne Ripley; Brian H Weinerman (Canadian Journal of Gastroenterology)
BACKGROUND: Some data suggest that there is an increased incidence of second malignancies associated with small bowel adenocarcinomas, but this has not been reviewed in the context of a tumour registry.